Pediatric meningiomas in Southwestern Nigeria: A single-institutional experience (2019)
BACKGROUND: Meningiomas are the second commonest intracranial tumors in many places worldwide. They are rare in the pediatric age group, however, and most studies have been able to document only a few patients. Meningiomas in pediatric patients have also been shown to behave differently from those in the adult population. This study was done to examine histologic types of meningiomas seen in pediatric patients from a predominantly African population using the 2016 World Health Organization (WHO) grading system for intracranial tumors. METHODS: Data from the operating logs of patients and histology reports of the samples sent to the pathology department during the study period were extracted. The data obtained were the age, sex, location of the intracranial tumor, histologic diagnosis, WHO grade, and tumor recurrence. RESULTS: Nine pediatric age patients were found among the 166 surgically excised meningiomas received at the pathology department in our institution over a 19-year period. The age range was from 8 months to 17 years. There was a male-to-female ratio of 1:2 with a female predominance. Six tumors were basally located. All tumors were WHO grade I, with transitional meningiomas being the commonest, followed by meningothelial. There was no history of recurrence in any of the tumors after complete surgical excisions. CONCLUSIONS: Our study showed the rarity of meningiomas in the study population, and there was a predominance of basally located tumors.